2004
DOI: 10.1111/j.1471-4159.2004.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptor agonists and antagonists mediate tolerance to kainic acid and reduce high‐affinity GTPase activity in young, but not aged, rat hippocampus

Abstract: Domoic acid acts at both kainic acid (KA) and a-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA)-sensitive glutamate receptors and induces tolerance against subsequent domoic acid insult in young but not aged rat hippocampus. To determine the receptor specificity of this effect, tolerance induction was examined in hippocampal slices from young and aged rats. Slices were preconditioned by exposure to low-dose KA to activate kainate receptors, or the AMPAreceptor selective agonist (S)-5-fluorowillardiine (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…The involvement of the excitatory amino acids kainate and AMPA receptors was evaluated and results demonstrated that the kainate receptor impairment had a pivotal role in basal synaptic transmission decrease. In control conditions, indeed, we showed that kainate perfusion, according to other authors (Sari and Kerr 2001;Hesp et al, 2004), induced in hippocampal slices transient neuronal hyperexcitability followed by pronounced depression of PS, while in MβCD-treated slices, these effects were totally prevented. These results were confirmed by the present finding that the kainate-induced intracellular calcium influx in pyramidale cell cultures was blocked by MβCD pretreatment, indicating for the first time that cholesterol directly affects kainate receptor activity.…”
Section: Discussionsupporting
confidence: 66%
“…The involvement of the excitatory amino acids kainate and AMPA receptors was evaluated and results demonstrated that the kainate receptor impairment had a pivotal role in basal synaptic transmission decrease. In control conditions, indeed, we showed that kainate perfusion, according to other authors (Sari and Kerr 2001;Hesp et al, 2004), induced in hippocampal slices transient neuronal hyperexcitability followed by pronounced depression of PS, while in MβCD-treated slices, these effects were totally prevented. These results were confirmed by the present finding that the kainate-induced intracellular calcium influx in pyramidale cell cultures was blocked by MβCD pretreatment, indicating for the first time that cholesterol directly affects kainate receptor activity.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, in rat hippocampal CA1, low concentrations of GYKI 52466, and NBQX-induced tolerance to the adverse electrophysiological effects of high-dose KA, even after the antagonists had been washed from the slice preparation. Taken together, our findings suggest that tolerance is triggered by a selective reduction in constitutive GPCR activity, and this metabotropic neuroprotective mechanism is lost in aged hippocampus (Hesp et al, 2004). Given the lasting and amplifying nature of metabotropic modulation, we hypothesized that GYKI 52466 may be effective in reducing seizure severity at doses well below those normally associated with adverse side effects.…”
Section: Introductionsupporting
confidence: 55%
“…In the course of assessing pharmacological preconditioning mechanisms, we found that in vitro preconditioning with GYKI 52466 induces a lasting tolerance versus kainic acid (KA) toxicity in hippocampal CA1, and that this effect may be metabotropic in nature (Hesp et al, 2004). In those studies we found that a number of ionotropic AMPA and KA antagonists (including GYKI 52466) also acted as inverse agonists of G-protein coupled receptor (GPCR) function, significantly reducing constitutive GTPase activity in hippocampal membranes from young but not aged rats.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Lefebvre et al (2009) showed that DA doses below those that cause observable signs of behavioral injury in zebrafish can downregulate several genes involved in important biochemical processes, suggesting potential neurological risk associated with asymptomatic DA exposures. In contrast, experiments with rats have demonstrated that low DA doses can precondition the brain and induce tolerance against higher DA doses in young, but not aged, rats (Kerr et al 2002, Hesp et al 2004. In humans, the most susceptible individuals to low DA doses may include pregnant and nursing women, since experiments with rats showed that (1) low DA doses may be transferred through milk and placenta, and accumulated in the amniotic fluid of pregnant rats and the brain of prenatal rats (Maucher & Ramsdell 2005, 2007; and (2) DA can reach the brain without restriction, causing neurological and behavior effects later in the life for prenatal rats (Dakshinamurti et al 1993, Levin et al 2005, Maucher & Ramsdell 2007.…”
Section: Discussionmentioning
confidence: 99%